Understanding Adolescence’s Experiences in Using “Study with Me” Content Video - Yunianto, Paramita; Putridinanti , Maudy (Universitas Muhammadiyah Yogyakarta, 2022)
The rise of technology is constantly evolving rapidly. Changes in behaviour have emerged in society as a result of technology growth. For instance, it can be easily influenced by content consumed in daily life, such as concepts changes in independent learning. When entering the quarantine for a long period of time, the changes in self-study behaviour begin to appear. Furthermore, when viewers require high concentration at home as well as they need to search for a good ambience at the same time so they will seek encouragement to learn in quarantine. One of the content is study with me on YouTube platform, which entails recording yourself doing independent learning activities over an extended period of time. This type of content has become extremely popular among millennials and gen Z generations. The usage of background or ambience in this content also plays an important function in capturing viewers' interest in understanding the subject. as a